2020
DOI: 10.1038/s41598-020-74165-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroless and contrast-free catheter ablation without a lead apron in routine clinical practice

Abstract: The technique of catheter ablation has been improved within the past few decades, especially by three-dimensional (3D) mapping system. 3D mapping system has reduced radiation exposure but ablation procedures still require fluoroscopy. Our previous study showed the safety and efficacy of catheter ablation based on intracardiac echogram combined with CARTOSOUND/CARTO3 system, however fluoroscopy use for an average of 16 min is required for this procedure. The present study was aimed to reduce radiation exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 24 publications
(38 reference statements)
0
30
0
Order By: Relevance
“…Recurrence‐free survival rates were reported in 12 studies 3,5,6,8,10–12,17–22 . Mean procedure times were reported in 15 studies 3–8,10–13,17–22 . Complication rates were reported in 13 studies 3–7,9,11–13,19–22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence‐free survival rates were reported in 12 studies 3,5,6,8,10–12,17–22 . Mean procedure times were reported in 15 studies 3–8,10–13,17–22 . Complication rates were reported in 13 studies 3–7,9,11–13,19–22 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the 16 studies included in this meta‐analysis (2105 ZF, 3715 CF/LF) 3–9,11,12,17,19–22 reported acute procedure success rates. There was no significant difference in acute procedure success between ZF and CF/LF (OR: 1.10, 95% CI: 0.75–1.59, I 2 : 0.0%, p = .628) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a recently published smaller study Matsubara et al 15 . described similar method of AF ablation using ICE/EAM automatic integration system with imaging of the LA with the ICE probe introduced transseptally in the LA.…”
Section: Discussionmentioning
confidence: 99%
“…ily. 14 The currently available technology renders zero-fluoroscopy ablation feasible. Nevertheless, the feasibility of this technique is limited by the expertise of the operator.…”
Section: Feasibility Of Performing Zerofluoroscopy Ablationmentioning
confidence: 99%